Challenges of Cargo Container Services in Major Ports in India - Subramanian, S.; Ilangovan, D. (Indian Journal of Marketing, 2007)
The impact of containerization in the economy of any nation cannot be over emphasized. To add the Indian container services is relatively in-efficient due to low level of productivity and inefficient processes and procedures when compared with its counterparts, The cost of handling containers through Indian ports is much higher than other regional ports like Bangkok, and Singapore. The hub of container industry in India viz., Cargo Container Service Stations maintained in the port complex do not live upto the expectations. The port labour often suspend their support by way of labour strike during traffic seasons.